Outcome following asphyxial insult in term neonates - Scher, L G (My University, 2014)
The admission records of all newborns admitted to the Johannesburg Neonatal Intensive Care Unit over a four year period with a birthweight >2000 grams and who were asphyxiated at birth and required ventilation were reviewed. Follow-up data were obtained from the Neonatal Follow-up Clinic files. Of the 109 newborns who fulfilled entry criteria, 73 (70%) were males, 36 (30%) females. The mean gestational age was 36 weeks (± 2,9), mean birthweight 2700g (± 555). Apgar score at 1 minute was 1-2 in 33% of the patients, 3-4 in 33% and 5-6 in the remaining 33%. Outcome was normal in 44 (40%), death occurred in 18 (15%) and neurological deficit was found in 6 (6%). Forty tnree (39%) were lost to follow up. It was shown that in subjects available for follow-up, seizures and cardiorespiratory complications of asphyxia (congestive cardiac failure/ tricuspid incompetence/ meconium aspiration syndrome/ persistent fetal circulation) were significantly associated with death or poor neurological outcome, whereas asphyxia (even requiring ventilation) without the latter signs and symptoms was predictive of good recovery.